Graduates' Unemployment In Malaysia : An Industrial Survey - Goh, Kim Chuan (2005)
This study demonstrates the causes that lead to graduates' unemployment in Malaysia. Important skills were highlighted in thi sresearch and their importance are then compared between both employers' and graduates' perception to find if there is an apparent mismatch.